Subnational Authorities as Key Global Actors - Matteo Fulgenzi (Athena)
The emerging role of subnational governments on the international scene, characterized by direct foreign engagements and participation in global networks, marks a pivotal shift in the architecture of world governance. This paper examines the essential role of local and regional authorities (LRAs) as key actors in advancing sustainable development, human rights protection, and democratic participation on a global scale, highlighting their involvement in the implementation of the UN 2030 Agenda and their multifaceted merits in conflict prevention and post-conflict reconstruction across the globe. Moving towards the analysis of the central role of Member States’ LRAs in the context of the EU/EEA legal framework – with their important contribution to the achievement of EU’s objectives both internally and in terms of external projection of the founding values and policies of the EU – this article delves into the dynamics and implications of the so-called paradiplomacy in order to shed light on how subnational actors are redefining the paradigms of traditional state-centric diplomacy. In such perspective, this work explores the relevant impact of informal diplomacy on international relations, international law, and global governance, emphasizing the innovative concepts of glocal diplomacy, global law, and glocal law and their significance for the pursuit of world peace and security.